LAWS OF BURGOS: 500 YEARS - Pizarro Zelaya, Antonio (2013)
The Laws of Burgos are the first known written labor Code of America.  They develop a general conception on relations between conquerors and conquered in the New World and therefore are the first colonial code of modern Europe.  They also enshrined the Encomienda and prescribe an extensive program of forced acculturation of Native Americans. In this paper, with a combination of anthropological approach and immanent critique, we analyze and discuss these two aspects and try to make an overall assessment of their impact on colonial society in the early sixteenth century.